2010
DOI: 10.3109/09513591003632118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overweight and underweight on IVF treatment in Chinese women

Abstract: At a lower cutoff point of BMI in Chinese women, overweight is associated with increased miscarriage risks and impaired response to ovarian stimulation after IVF and ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 41 publications
(77 reference statements)
3
45
0
Order By: Relevance
“…Several studies have demonstrated decreased odds of CP in patients with higher BMI (9,10,16,31). However, many more studies have failed to identify a statistically significant difference (7,8,20,(25)(26)(27)(28)(29)(30), including two meta-analyses of 21 and 13 studies that demonstrated a lower chance of CP with obesity (32,33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have demonstrated decreased odds of CP in patients with higher BMI (9,10,16,31). However, many more studies have failed to identify a statistically significant difference (7,8,20,(25)(26)(27)(28)(29)(30), including two meta-analyses of 21 and 13 studies that demonstrated a lower chance of CP with obesity (32,33).…”
Section: Discussionmentioning
confidence: 94%
“…The majority of those studies had much smaller sample sizes, ranging from 72 to 278, and used binomial BMI classifications (10,(25)(26)(27). Two other studies included only Asian patients and three BMI categories (28,29), and Dokras et al analyzed data only from patients <38 years old (30).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore a negative effect of abnormal BMI on clinical outcome cannot be excluded. Despite the differences between IVM and IVF cycles, our results should also be considered in the context of previous studies investigating effect of BMI on IVF outcomes, as both treatments also share common steps to successful implantation and delivery [3][4][5][6][7]20,21].…”
Section: Discussionmentioning
confidence: 95%
“…However, studies investigating the effect of obesity on IVF outcome have yielded contradictory results [3,4,6,7]. Variations in the results can be attributed to different study populations, random effects due to small sample sizes in some studies, different cut-off values of Body Mass Index (BMI) used to categorize participants, varying definitions of relevant outcome measures including pregnancy and miscarriage, and the lack of adjustment for potential confounders such as female age, the presence of Polycystic Ovarian Syndrome (PCOS), number of prior failed cycles in some studies [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Women with a low BMI (under 20, 19, or 18.5, depending on the study) have lower clinical pregnancy rates than normal weight women [17]. Underweight women also have an increased risk of miscarriage: a retrospective analysis of 594 patients showed pregnancy loss was 11% for underweight women compared to 0.5% for those with normal BMI [6 & ].…”
Section: Bmimentioning
confidence: 99%